The impact of interventions to promote healthier ready‐to‐eat meals (to eat in, to take away or to be delivered) sold by specific food outlets open to the general public: a systematic review. (29th November 2016) - Hillier‐Brown, F. C.; Summerbell, C. D.; Moore, H. J.; Routen, A.; Lake, A. A.; Adams, J.; White, M.; Araujo‐Soares, V.; Abraham, C.; Adamson, A. J.; Brown, T. J.
Summary: Introduction: Ready‐to‐eat meals sold by food outlets that are accessible to the general public are an important target for public health intervention. We conducted a systematic review to assess the impact of such interventions. Methods: Studies of any design and duration that included any consumer‐level or food‐outlet‐level before‐and‐after data were included. Results: Thirty studies describing 34 interventions were categorized by type and coded against the Nuffield intervention ladder: restrict choice = trans fat law ( n = 1), changing pre‐packed children's meal content ( n = 1) and food outlet award schemes ( n = 2); guide choice = price increases for unhealthier choices ( n = 1), incentive (contingent reward) ( n = 1) and price decreases for healthier choices ( n = 2); enable choice = signposting (highlighting healthier/unhealthier options) ( n = 10) and telemarketing (offering support for the provision of healthier options to businesses via telephone) ( n = 2); and provide information = calorie labelling law ( n = 12), voluntary nutrient labelling ( n = 1) and personalized receipts ( n = 1). Most interventions were aimed at adults in US fast food chains and assessed customer‐level outcomes. More 'intrusive' interventions that restricted or guided choice generally showed a positive impact on food‐outlet‐level and customer‐level outcomes. However, interventions that simply provided information or enabled choice had a negligible impact. Conclusion: Interventions to promote healthier ready‐to‐eat meals sold by food outlets should restrict choice or guide choice through incentives/disincentives. Public health policies and practice that simply involve providing information are unlikely to be effective.